Structure formation in the universe - Bartelmann, Matthias (Principles of evolution, 2011)
Two simple symmetry assumptions combined with general relativity lead to the class of Friedmann cosmological models on which the standard model for the structure and the evolution of the Universe is built. Within this model, dark matter dominates structures on the scales of galaxies and larger, and dark energy has dominated the expansion of the Universe since about half its present age. This chapter summarizes how cosmic structures could have developed under these circumstances and what they are characterized by. As to the origin of cosmic structures, the scenario of an early inflationary phase suggests that they arose from vacuum fluctuations of a primordial quantum field.
Gesehen am 22.09.2017